2015
DOI: 10.1175/jpo-d-13-0274.1
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal-Scale Freshening at the Salinity Minimum in the Western Part of North Pacific: Importance of Wind-Driven Cross-Gyre Transport of Subarctic Water to the Subtropical Gyre

Abstract: Using oceanographic observations and an eddy-resolving ice-ocean coupled model simulation from 1955 to 2004, the effects of the wind-driven ocean circulation change that occurred in the late 1970s during multidecadal-scale freshening of the North Pacific Intermediate Water (NPIW) at salinity minimum density (;26.8 s u ) were investigated. An analysis of the observations revealed that salinity decreased significantly at the density range of 26.6-26.8 s u in the western subtropical gyre, including the mixed wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…Indeed, the intensity of the AL, defined as the minimum of the wintertime mean sea level pressure field within the region bounded by 30°N–60°N and 150°E–150°W, strengthened over the period 1950–2015 (Figure b; updated from Sugimoto & Hanawa, ). In a model simulation, Nakanowatari et al () demonstrated that the southwestward flow of the Oyashio along the Kuril Islands was stronger over 1977–2004 relative to 1955–1976, and they suggested that the intensification of the subarctic gyre would be related to the strengthening of the AL. It implies that the contribution of the WSAW to the Oyashio may have increased because of strengthening of the AL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the intensity of the AL, defined as the minimum of the wintertime mean sea level pressure field within the region bounded by 30°N–60°N and 150°E–150°W, strengthened over the period 1950–2015 (Figure b; updated from Sugimoto & Hanawa, ). In a model simulation, Nakanowatari et al () demonstrated that the southwestward flow of the Oyashio along the Kuril Islands was stronger over 1977–2004 relative to 1955–1976, and they suggested that the intensification of the subarctic gyre would be related to the strengthening of the AL. It implies that the contribution of the WSAW to the Oyashio may have increased because of strengthening of the AL.…”
Section: Discussionmentioning
confidence: 99%
“…In the Pacific, the periodic shift of the Pacific Decadal Oscillation (PDO) in 1977/78 could explain the freshening of the North Pacific Intermediate Water (NPIW) in the recent decades. This significant decrease is associated with an increase in southward transport of Oyashio water, corresponding to the deepened Aleutian Low (Nakanowatari et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In support of this mechanism, Joyce and Dunworth‐Baker [] attributed multidecadal cooling and freshening of subsurface water within the transition area to a southward shift of the Kuroshio Bifurcation Front, which leads to a southward transport of cold and fresh subpolar water to the transition area [ Nakanowatari et al ., ]. Likewise, a southward shift in the southern boundary of the subtropical gyre [ Chen and Wu , ] may replace relatively cold and fresh North Equatorial Current between 10° and 20°N with warmer and saltier subtropical water, thereby explaining increasing temperature and salinity within the southern periphery of the subtropical gyre.…”
Section: Historical Temperature and Salinity Trendsmentioning
confidence: 99%
“…The northern boundary of the North Pacific subtropical gyre is located around 45°N corresponding to the maximum strength of the westerlies, while the southern boundary is around 15°N corresponding to the maximum strength of the trade winds. The strength and position of the midlatitude and low‐latitude winds have varied over multidecadal timescales, with far‐reaching impacts on the physical properties of seawater within gyre boundaries, and North Pacific marine ecosystems and climate [e.g., Mantua et al ., ; Deser et al ., ; Joyce and Dunworth‐Baker , ; Kwon et al ., ; Chen and Wu , ; Nakanowatari et al ., ].…”
Section: Introductionmentioning
confidence: 99%